Criminal Liability for Mystical Ritual Fraud: Applying the Principle of No Punishment Without Fault - Munawwar Kholis; Rasyid Saliman Bin Muhammad Arsyad Midin; Enny Agustina (Lembaga Riset Ilmiah, 2026)
Fraud involving mystical ritual schemes presents a distinctive challenge to criminal law because it intersects with legally protected freedom of belief and the prohibition of deceptive conduct. While existing studies on fraud and criminal liability generally focus on conventional forms of deception, limited attention has been given to the application of the principle of no punishment without fault (geen straf zonder schuld) in cases where religious, spiritual, or mystical claims are used as instruments of manipulation. This study addresses this gap by examining how criminal fault can be distinguished from the exercise of spiritual belief and ritual practices, particularly in determining criminal responsibility for mystical ritual fraud. This study aims to analyze the application of the principle of no punishment without fault (geen straf zonder schuld) in determining criminal responsibility for fraud committed through mystical ritual schemes, the forms of criminal liability applicable to offenders, and the factors considered by judges in determining criminal fault. This research employs normative legal research using statutory, conceptual, case, and comparative approaches. The legal materials consist of primary sources, including the Indonesian Criminal Code, Law Number 1 of 2023 concerning the National Criminal Code, and criminal procedure regulations, while secondary sources include criminal law doctrines, academic journals, and relevant legal literature concerning criminal responsibility. The collected legal materials are analyzed qualitatively through systematic and conceptual interpretation to examine the relationship between criminal elements, fault, and criminal liability. The findings indicate that the principle of no punishment without fault functions as a juridical limitation to ensure that criminal punishment is not imposed against spiritual beliefs or ritual practices themselves, but against the intentional use of such practices as instruments of deception or false representations to obtain unlawful benefits. The study develops a conceptual framework in which criminal fault is assessed through the interaction of actus reus, mens rea, the offender’s capacity for responsibility, and the causal connection between deceptive claims and the victim’s transfer of property. Criminal responsibility for offenders is established based on the fulfillment of fraud elements, the existence of intention (mens rea), criminal capacity, and the absence of justification or excuse defenses. Judges must evaluate various indicators in determining criminal fault, including communication patterns, claims of supernatural abilities, the use of ritual symbols, financial demands, the causal relationship between mystical claims and property transfers, and the offender’s conduct after obtaining benefits. Theoretically, this framework contributes to Indonesian criminal law by refining the application of geen straf zonder schuld to belief-based forms of fraud without criminalizing belief itself. Practically, it provides guidance for judges and law enforcement authorities in distinguishing legitimate spiritual practices from intentional criminal manipulation and offers a basis for more precise future criminal-law policy concerning fraud involving mystical or belief-based practices. This study emphasizes that criminal law does not seek to prove the existence or non-existence of supernatural powers but evaluates whether such claims have been deliberately used as manipulative instruments causing harm to victims.